A Post-Opening Transport Infrastructure's Socio-Economic Evaluation: The Case of "Attiki Odos Motorway" - A. Belegri-Roboli; Th. Marinos; M. Markaki (European Regional Science Association (ERSA), 2013)
The purpose of this research is the post-opening evaluation of "Attiki Odos Motorway" (AOM) socio-economic impacts, during the period of its operation. The AOM is the peripheral ring-road of the metropolitan Athens-Attica area. To this end, the study estimates an ex post project's "Overall Returns Index" (ORI) based on Multi-Criteria Analysis (MCA). Within this framework, selected factors-criteria specified by the interaction mechanism between the motorway's operation and its socio-economic environment are assessed. Then, at each criterion a number of sub-criteria that characterize it are assigned. These are evaluated not on the basis of subjective judgments - as in the case of the traditional MCA - but on the basis of performance indexes, supported by factual dataset. With regard to the empirical results, the socio-economic returns of the studied motorway, as they occurred from the formula, are high. This means that, on average, the selected sub-criteria and thus the criteria of the formula appear high compliance in our case study. However, the estimates are subject to the limitation of the methodology employed as well as other factors. Clearly, future research on the subject would be of great interest. Keywords: "Attiki Odos Motorway", socio-economic impacts, Multi-Criteria Analysis, Overall Returns Index.
Keywords: R11; R42; 330; "Attiki Odos Motorway"; socio-economic impacts; Multi-Criteria Analysis; Overall Returns Index